1865 Ma tholeiitic magmatism during an extensional episode of the Svecofennian orogeny: the Kaiplot gabbros in Nagu (Nauvo), southwestern Finland - Olav Eklund; Jussi S. Heinonen (Bulletin of the Geological Society of Finland, 2025)
The Svecofennian orogeny in southern Finland has traditionally been divided into two broadly defined compressional stages, the 1.89–1.87 Ga “synorogenic” stage and the ca 1.84–1.81 Ga “lateorogenic” stage. The term “intraorogenic” is used to describe a less studied stage that occurred between these two, with some overlap with both. Mafic and intermediate intrusions collectively named as the Kaiplot gabbros are situated on a number of islands and islets in Nagu (Nauvo) in the southwestern archipelago of Finland. The outcrops occur as dykes as well as plutonic bodies and have been emplaced in at least two separate pulses. Net-veining and other structures suggesting incomplete mixing between mafic and felsic magmas are found. The main plutonic body is a hornblende gabbronorite. U-Pb dating (TIMS, zircon) gives it an age of 1865 ± 2 Ma. Geochemically, the most primitive Kaiplot gabbros are tholeiitic and show affinity to back-arc basin basalts, indicating generation in an extensional tectonic environment. Their parental magmas appear to have originated from relatively high-degree partial melting of a shallow spinel-bearing and slightly subduction-modified depleted mantle. During transport and emplacement, both differentiation and assimilation of crustal material have taken place. The Kaiplot gabbros endorse an extensional tectonic episode of the Svecofennian orogeny at around 1865 Ma, possibly as a result of tectonic switching propagating southwestwards.